2017
DOI: 10.1016/s2213-8587(16)30107-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maternal obesity on the long-term health of offspring

Abstract: Alongside its immediate implications for pregnancy complications, increasing evidence implicates maternal obesity as a major determinant of health in the offspring during childhood and later adult life. Observational studies provide evidence for effects of maternal obesity on the offspring's risks of obesity, coronary heart disease, stroke, type 2 diabetes and asthma. Maternal obesity may also lead to poorer cognitive performance in the offspring and an increased risk of neurodevelopmental disorders including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
615
2
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 763 publications
(654 citation statements)
references
References 109 publications
20
615
2
17
Order By: Relevance
“…On average, the women in the 1990s cohort began pregnancy within the overweight category, whereas those in the 2010s cohort did so within the obesity category. Given that maternal obesity confers important adverse outcomes for both the mother and the child, and possibly for future generations, 21 this epidemic rise in obesity threatens the progress in pregnancy outcomes that has already achieved. It also puts at risk the attainability of the goals for reducing the burden of non-communicable diseases by 2025, a challenge faced by Brazil and all other nations.…”
Section: Discussionmentioning
confidence: 99%
“…On average, the women in the 1990s cohort began pregnancy within the overweight category, whereas those in the 2010s cohort did so within the obesity category. Given that maternal obesity confers important adverse outcomes for both the mother and the child, and possibly for future generations, 21 this epidemic rise in obesity threatens the progress in pregnancy outcomes that has already achieved. It also puts at risk the attainability of the goals for reducing the burden of non-communicable diseases by 2025, a challenge faced by Brazil and all other nations.…”
Section: Discussionmentioning
confidence: 99%
“…Women who were obese and experienced GDM have an increased risk of later-life diabetes and CVD. Offspring of obese mothers have increased long-term risks of obesity, diabetes, and CVD [305]. Interestingly, in a population level study of Caucasian and First-Nation Canadians with 24 years of follow-up, initiation of breastfeeding prior to hospital discharge was associated with a significant reduction in the risk of subsequent maternal diabetes in both mothers who had and not had GDM [306].…”
Section: Consensus Recommendationsmentioning
confidence: 99%
“…The possibility that maternal obesity promotes asthma in the child by leveraging both inflammatory and metabolic pathways has been gaining momentum over the last few years [37]. A meta-analysis of 14 studies and 108,321 mother-child pairs showed that maternal overweight or obesity in pregnancy was associated with increased risks of childhood asthma or wheeze ever (OR 1.31, 95% CI 1.16, .49) and current asthma or wheeze (1.21, 1.07, .37), independent of offspring body mass index (BMI) [38].…”
Section: Maternal Obesitymentioning
confidence: 99%